The Chronology of the Ganeshwar Jodhpura Culture: A Reassessment Based on Graffiti and Cross-Cultural Comparisons. (28th June 2021) - Prasad, Esha; Singh, Ravindra Nath
The Ganeshwar-Jodhpura Chalcolithic culture was first discovered in the 1970's post the excavation at Jodhpura and Ganeshwar respectively. However over the years, one of the major drawbacks in the study of the culture is the dating and periodisation. This paper on the basis of ceramic analysis and comparative studies of graffiti is an attempt to divide the site of Ganeshwar into two periods viz. the Early and Mature Period and proposes a new chronology. The characteristics features specifically in terms of ceramics of both the periods have been defined.